PENGARUH SISTEM INFORMASI AKUNTANSI PENGGAJIAN TERHADAP EFEKTIVITAS PENGENDALIAN INTERNAL GAJI KARYAWAN - Supriani Supriani; Baiq Anggun Hilendri L; L. Takdir Jumaidi (Bisnis-Net, 2023)
This research was conducted to see the level of use of the payroll accounting information system that has been implemented by the Bureau of Logistics Bureau of the West Nusa Tenggara regional division regarding the system for recording and calculating payroll which is carried out using the Enterprise Resource Planning (ERP) system and the Payroll system component in the ERP system as a payment system. The researcher aims to determine the effect of the payroll accounting information system on the internal control of employee salary payments at the regional division of the Regional Bureau of Logistics Housing Bureau of West Nusa Tenggara. The sample in this study was 40 employees who were taken based on a purposive sampling technique or several criteria; 1) Located and placed in the NTB regional office, 2) Has duties or positions in the SPI, HR, and finance sections in the NTB regional office, and 3) Has worked for more than one year. Data analysis in this study used SPSS 26 to test the research instrument and used simple linear regression analysis. The results showed that the payroll accounting information system variable had a t count of 8.296 > t table of 2.021 (sig. α/2=0.05/2=0.025 and df=40) with an unstandardized beta coefficient of 0.803 and a significance level of 0.0000 smaller than 0.05, then H1 is accepted. This means that the accounting information system has a significant positive effect on the effectiveness of internal control over employee salaries. Thus the hypothesis in this study is declared proven or accepted. This shows that the higher the use of the payroll accounting information system, the higher the level of effectiveness of internal control of employee salaries at Perum Bulog. Keywords: Accounting Information System, payroll and Internal Control System Effectiveness